Rapid identification of organophosphorus pesticides on contaminated skin and confirmation of adequate decontamination by ambient mass spectrometry in emergency settings. (8th February 2020) - Su, Hung; Yeh, I‐Jeng; Wu, Yen‐Hung; Jiang, Zong‐Han; Shiea, Jentaie; Lee, Chi‐Wei
Abstract : Rationale: Dermal exposure to pesticides may cause severe intoxication and even result in a fatal outcome. To expedite rescue in the emergency department, it is mandatory to develop a point‐of‐care analytical method for immediate identification of pesticides on the skin of exposed personnel, and to perform immediate dermal decontamination to prevent further harm and optimize the chance for full clinical recovery. Methods: Four of the most commonly used highly toxic pesticides that contaminate the skin were rapidly characterized by thermal desorption electrospray ionization mass spectrometry. The technique was also applied to confirm the completeness of pesticide decontamination from the skin. Pesticide sampling, desorption, ionization, and detection altogether took less than 30 s. In addition, different fabrics of protective garments worn by farmers were assessed with this efficient ambient mass spectrometric technique for their protective capabilities against dermal exposure to pesticides, and scanning electron microscopy was used to observe their different microstructures. The decontaminating efficacies of different cleansing agents for these skin contaminants were also evaluated by this technical platform. Results: The repeatability of this method had a low relative standard deviation (<22%) for the detection of pesticides on the surface of swine skin. The detection limits of the pesticides in solution were found to be in the range of 3–20 ng/mL. Linearity was observed between the signal intensities and the concentrations of the four pesticides in solution within the range of 50 ng/mL to 50 μg/mL (R 2 between 0.9921 and 0.9966). In addition, it was found that PVC fabric is optimal in preventing skin contamination by fenthion and detergent had the best efficiency for fenthion decontamination. Conclusions: Since the whole analytical process is extremely fast, this technique allows early point‐of‐care identification of contaminating pesticides on the skin of exposed patients in the emergency room, as well as rapid assessment of the adequacy of decontamination.